Low energy emulsion-based fermentation enabling accelerated methane mass transfer and growth of poly(3-hydroxybutyrate)-accumulating methanotrophs. (May 2016) - Myung, Jaewook; Kim, Minkyu; Pan, Ming; Criddle, Craig S.; Tang, Sindy K.Y.
Highlights: An emulsion effectively increases interfacial area enhancing delivery of methane. Emulsion-based delivery of methane is comparable to intense mixing. Methanotroph growth in emulsions is reaction-rather than diffusion-limited. Microfluidics did not negatively affect cell division or P3HB accumulation. Nanoparticles can replace surfactant in stabilizing methanotroph-growing emulsions. Abstract: Methane is a low-cost feedstock for the production of polyhydroxyalkanoate biopolymers, but methanotroph fermentations are limited by the low solubility of methane in water. To enhance mass transfer of methane to water, vigorous mixing or agitation is typically used, which inevitably increases power demand and operational costs. This work presents a method for accelerating methane mass transfer without agitation by growing methanotrophs in water-in-oil emulsions, where the oil has a higher solubility for methane than water does. In systems without agitation, the growth rate of methanotrophs in emulsions is five to six times that of methanotrophs in the medium-alone incubations. Within seven days, cells within the emulsions accumulate up to 67 times more P3HB than cells in the medium-alone incubations. This is achieved due to the increased interfacial area of the aqueous phase, and accelerated methane diffusion through the oil phase.